Microbial Decomposition of Lignin to Methane Reduces Net Blue Carbon Benefit Across China's Saltmarshes - Leilei Xiao; Chuancheng Fu; Isaac R. Santos; Carlos M. Duarte; Jian Liu; Lifeng Zhou; Meng Zhou; Run Dang; Jinkuo Lin; Kai Xiao; Yongming Luo; Guangxuan Han (Global Change Biology, 2026)
CH 4 emissions from mangrove, saltmarsh, and seagrass ecosystems partially offset carbon sequestration, potentially diminishing the climate mitigation capacity of these blue carbon habitats. However, a mechanistic understanding of the processes governing CH 4 production potential across large spatial scales remains limited. By integrating incubation‐based measurements from 116 sites, we reveal significant ecosystem‐specific differences in CH 4 production potential, with saltmarshes emerging as CH 4 production hotspot relative to mangroves and seagrass meadows. Using an integrated analytical approach encompassing more than 30 environmental, biogeochemical, and microbial parameters, we demonstrate that CH 4 production potential converges on sediment organic carbon availability, particularly plant‐derived carbon, as a key regulatory axis. Additionally, metagenome‐assembled genomes (MAGs) recovered from saltmarshes show a functional bias toward lignin degradation, thereby fueling downstream CH 4 production via methylotrophic pathways. Lignin‐addition and stable carbon isotope experiments further provide supportive evidence that lignin decomposition enhances Chinese saltmarsh CH 4 production potential, revealing a pathway that may reduce net blue carbon benefit. Together, these findings underscore that saltmarsh plant‐derived lignin is less stable than conventionally assumed, as microbial processing redirects stored carbon toward CH 4 production, challenging current blue carbon accounting frameworks at a continental scale within China.